Phase variation in Salmonella: genetic analysis of a recombinational switch. - Silverman, M (1979)
The alternative expression of Salmonella genes H1 and H2, which specify different flagellar antigens, results in the oscillation of phenotype known as phase variation. This alternation is controlled by the inversion of an 800-base-pair sequence of DNA adjacent to, or including part of, the H2 gene. The invertable region was presumed to regulate the function of a promoter and to include specific sites at which a recombinational event, resulting in the inversion, could occur. Here we report genetic manipulations of hybrid lambda phage carrying the H2 gene that were used to define the H2 promoter region and the recombinational sites. The H2 gene fragment was inserted on a hybrid lambda phage next to the cheW gene, which lacked a promoter element. In the resulting fusion, cheW gene activity was restored, the expression of the H2 and cheW genes was controlled coordinately by the inversion, and the polarity of transcription and location of the H2 gene could be determined. Evidence from this type of gene fusion suggested that the H2 gene promoter is included in the inversion region. Hybrid H2 phage were constructed that contained substitutions for regions of the H2 gene. In contrast to hybrid lambda containing the H2 gene, which alternate between "on" and "off" states, several substituted lambdaH2 were fixed in the "on" state. A site necessary for the recombinational event must have been removed in these fixed lambdaH2.